Placer por la música y su relación con la anhedonia social - García-Rodríguez, María; Fernández Company, José Fernando; Alvarado, Jesús M.; Jimenez, Virginia; Ivanova-Iotova, Anelia (Studies in psychology, 2021)
El principal objetivo de esta investigación fue evaluar si la ausencia de placer hacia la música o anhedonia musical, forma parte del constructo psicológico de anhedonia (DSM-5), o si, por el contrario, se trata de constructos independientes como se ha planteado desde la neurociencia cognitiva. Para valorar esta cuestión, se crearon seis composiciones musicales inéditas para evocar emociones básicas. 153 profesionales de la música y 303 estudiantes (M = 17.58 años, SD = 4.16) evaluaron su nivel de arousal y valencia, pudiéndose constatar una alta consistencia entre los resultados de ambos grupos. Posteriormente, mediante un modelo de ecuaciones estructurales, se observó una alta correlación estadísticamente significativa (r = .63, p < .001) entre las medias latentes de valencia (placer que evocan los fragmentos musicales) y la Escala de Placer Anticipatorio y Consumatorio (ACIPS) utilizada para medir niveles de anhedonia social. Además, el placer social mantiene correlaciones inversas con las emociones de los fragmentos musicales de valencia negativa (Enfado, Miedo y Asco), lo que permite concluir que la anhedonia musical está fuertemente relacionada con la anhedonia social.
Pleasure in music and its relationship with social anhedonia
The purpose of this study was to evaluate whether the inability to feel pleasure towards music — or musical anhedonia — is part of the psychological construct of anhedonia (DSM-5) or whether they are both independent constructs, as suggested by the field of cognitive neuroscience. To assess this objective, six unpublished musical compositions were created to evoke basic emotions. We analysed the level of arousal and valence in a sample of 153 music professionals and 303 students (M = 17.58 years, SD = 4.16) and were able to verify a high consistency between the results of both groups. By using a structural equation model, we subsequently observed a statistically significant high correlation (r = .63, p < .001) between the latent means of valence (pleasure evoked by musical fragments) and levels of social anhedonia, measured by the Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS). Furthermore, social pleasure maintained inverse correlations with the emotions of negative valence (Anger, Fear and Disgust) provoked by musical fragments, which allowed us to conclude that musical anhedonia is strongly related to social anhedonia.
Keywords: placer; anhedonia social; anhedonia musical; valencia; arousal; WOS(2)